Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acs.jnatprod.9b00755
|View full text |Cite
|
Sign up to set email alerts
|

Ealamines A–H, a Series of Naphthylisoquinolines with the Rare 7,8′-Coupling Site, from the Congolese Liana Ancistrocladus ealaensis, Targeting Pancreatic Cancer Cells

Abstract: From the twigs and leaves of the Central African liana Ancistrocladus ealaensis (Ancistrocladaceae), a series of ten 7,8′-coupled naphthylisoquinoline alkaloids were isolated, comprising eight new compounds, named ealamines A−H (4a, 4b, 5−10), and two known ones, 6-O-demethylancistrobrevine A (11) and yaoundamine A (12), which had previously been found in related African Ancistrocladus species. Only one of the new compounds within this series, ealamine H (10), is a typical Ancistrocladaceae-type alkaloid, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 77 publications
0
6
1
Order By: Relevance
“…To investigate the possible potential axial chirality in dimeric pimprinine molecules, CD spectra for dipimprinines A-D (1-4) were acquired (Figures S10, S18, S26, S34). Unlike the reported natural dimeric atropisomers (Wang et al, 2013;Tshitenge et al, 2019), no Cotton effects can be found in any CD spectra of dipimprinines A-D (1-4). Consequently, either dipimprinines A-D (1-4) have no atropisomeric stereochemistry (that's to say a plane structure) or they were all racemates.…”
Section: Resultscontrasting
confidence: 75%
“…To investigate the possible potential axial chirality in dimeric pimprinine molecules, CD spectra for dipimprinines A-D (1-4) were acquired (Figures S10, S18, S26, S34). Unlike the reported natural dimeric atropisomers (Wang et al, 2013;Tshitenge et al, 2019), no Cotton effects can be found in any CD spectra of dipimprinines A-D (1-4). Consequently, either dipimprinines A-D (1-4) have no atropisomeric stereochemistry (that's to say a plane structure) or they were all racemates.…”
Section: Resultscontrasting
confidence: 75%
“…The activities against the CQ-sensitive NF54 strain showed IC 50 values of 6.3, 4.9, 0.84 and 22.2 μM, respectively. Meanwhile, compounds 26, 27 and 29 inhibited the CQ-and pyrimethamine-resistant K1 strain with IC 50 values of 1.6, 1.4, and 8.2 μM, respectively [67].…”
Section: Promising Anti-malarial Compounds Derived From the African F...mentioning
confidence: 98%
“…Among the compounds identified from Ancistrocladaceae, Tshitenge et al also isolated four naphthylisoquinolines, named ealamines A-D (26 to 29, Fig. 8) from the twigs and leaves of Ancistrocladus ealaensis (Ancistrocladaceae) harvested in Mbandaka, DR Congo [67]. These compounds were tested against CQ-sensitive NF54 and CQ-and pyrimethamine-resistant K1 strains of P. falciparum.…”
Section: Promising Anti-malarial Compounds Derived From the African F...mentioning
confidence: 99%
“…Ancistrocladus likoko , widely distributed in the North-Central region of the Congo Basin, produces 5,8′-coupled monomeric naphthylisoquinoline alkaloids exclusively, even in large quantities, along with a few 6′,6″-coupled dimeric analogues (referred to as michellamine-type dimers), which occur in very low concentrations. , The West-Central Congolese liana A. congolensis likewise contains 5,8′-linked monomeric naphthylisoquinoline alkaloids and michellamine-type dimers, but it additionally provides 5,1′- and 7,1′-coupled monomers. , A. ileboensis and A. ealaensis , by contrast, are much more “creative”, both at the monomeric and the dimeric level. The former one, endemic to the Southern Congo Basin, was shown to contain a number of 7,1′-, 5,1′-, 5,8′-, and 7,8′-connected monomers and several symmetric 3′,3″-coupled and the unsymmetric 3′,6′′-coupled dimers of 7,1′-linked monomers. ,, Ancistrocladus ealaensis from the North-Western region of the DRC was demonstrated to produce 5,8′-, 7,8′-, and N,C -coupled monomers and representatives of four subclasses of dimeric naphthylisoquinoline alkaloids: michellamine-type, korundamine-type (i.e., 6′,6″-coupled dimer with two different, 5,8′- and 7,8′-connectivities, at the outer axes), open-chain mbandakamine-type, and cyclombandakamine-type dimers. ,, …”
Section: Resultsmentioning
confidence: 99%